Exploring disparities and novel insights into metabolic and cardiovascular comorbidities among COVID-19 patients in Mexico - López-Cuevas, Jonathan Ariel; Martínez-García, Mireya; Hernández-Lemus, Enrique; Anda-Jáuregui, Guillermo de (Frontiers in Public Health, 2023)
During the previous years, particularly at the beginning of the COVID-19 pandemic, the potential role of metabolic and cardiovascular comorbidities in the severity and lethality of SARS-CoV2 infection has been widely discussed, often describing ambiguous outcomes. Here we investigate the prevalence of metabolic and cardiovascular comorbidities among COVID-19 patients in Mexico. Using a retrospective observational study design, data was collected from official databases of COVID-19 patients admitted to public and private hospitals in Mexico City. Our study found a discordant prevalence of metabolic and cardiovascular comorbidities among COVID-19 patients, particularly obesity, hypertension, and diabetes. Discordance consists in geographic location-dependent over and under-representation phenomena, that is the prevalence of such comorbidities in COVID-19 patients was significantly over or under the reported value for the general population in each location. These findings highlight the importance of screening for metabolic and cardiovascular comorbidities in COVID-19 patients and suggest the need for tailored interventions for this population. The study also provides insights into the complex relationships between COVID-19 and metabolic and cardiovascular comorbidities, which may inform future research and clinical practice.